Starting a Conversation or Sending a Message: The Uses & Abuses of State Anti-BDS Speech - Danielle Haberer (Washington University Journal of Law & Policy, 2018)
This note explores the language used by state actors through legislation and executive orders responding to the Boycott, Divestment, and Sanctions (BDS) movement. While the constitutionality of such laws has been questioned, Haberer argues the debate should focus on state speakers’ social and civic duty to welcome conversation rather than to send a specific message against the BDS movement. Haberer suggests that state speech can be improved in this area by avoiding problematic tactics such as “conversation stoppers” and aggressive, militarized language.
Keywords: First Amendment; boycott; divestment; sanctions; Israel; solidarity; Anti-Defamation League; anti-semetism; Title VI; Civil Rights Act; Department of Education; hostile environment; campus; state action; state speech; government speech doctrine; conversation stoppers; motives; acts; sending a message